Strategy of Former Indonesian Migrant Workers From Qatar in The Era of The Covid-19 Outbreak - Rochmaedah, Dedeh; Basrowi, Basrowi; Suseno, Bambang Dwi (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2022)
This study aims to analyze and investigate former migrant workers who previously worked in the country of Qatar, after the Covid-19 pandemic hit this country. The Qatar government has cut spending by 30% to shore up its finances amid the stress of the pandemic. The impact of the Qatari government's policy has resulted in the termination of the employment relationship of several Indonesian migrant workers in Qatar, some of the Indonesian migrant workers working in Qatar who brought their families while living in Qatar had to return to their homeland. This study aims to describe how retired Indonesian workers from Qatar have adapted to changing socio-economic conditions after they no longer work as migrant workers and return to Indonesia and their families in a state of not having a job during the COVID-19 pandemic. The method used in this research is qualitative research, which describes the problems to be studied based on actual social facts. The author uses primary data in this study, namely, through direct observation and interviews with retired Indonesian migrant workers from Qatar and their families as informants. The results of the study show that the socio-economic adaptation strategies of retired Indonesian workers from Qatar in the pandemic era are first, reducing expenses or living costs, secondly opening entrepreneurship, thirdly increasing productive assets, fourth working again in domestic and foreign companies